Numerical analyses of the effect of heterogeneities on rock failure process - Valley, Benoît; Suorineni, F.T.; Kaiser, P.K. (American Rock Mechanics Association, 2010)
While heterogeneities in strength and deformation properties are thought to play an important role in the failure processes of rocks and rock masses, they are rarely explicitly introduced in numerical models. This paper present the results obtained by introducing heterogeneities in a Finite Element Modeling tool (Phase2TM). Particularly the effect of heterogeneities in rock modulus and strength are investigated at the laboratory test sample scale. Limited modulus variability (coefficient of variation smaller than 1.5%) is sufficient to generate rock behaviour that is highly affected by induced tensile stress conditions. This variability in modulus reduces the peak strength and the post-peak strength drop: with increasing heterogeneity in deformability, the rocks become less brittle (i.e., more strain-softening). However, the brittleness in the low confinement range, leading to spalling behaviour, is enhanced by this heterogeneity. Various loading case and geometries are investigated highlights the influence of rock and rock mass heterogeneities. Modulus heterogeneities generate tensile conditions and damage when taking core samples from relatively high stress conditions. This may influence the samples strength and lead to an underestimation of the in-situ rock strength at depth. Heterogeneities influence the failure pattern around opening, with practical implication on ground support requirements. An equivalent homogeneous properties concept, as used for example by the GSI system, doesn't properly capture the failure pattern generated by the presences of heterogeneities, suggesting that the approach of ” equivalent” homogenous material could be inadequate and that heterogeneities should be introduced explicitly in numerical analyses of geomechanics problems.
2023